Solid-waste-based permeable crystallization waterproof functional aggregate as well as preparation method and application thereof
By using solid waste-based permeable crystal waterproof functional aggregate, the problem of difficult to achieve solid waste resource utilization and self-repair and waterproofing of cement-based permeable crystal materials in the prior art is solved, and the low-carbon resource utilization of solid waste materials and the efficient waterproofing and durability improvement of concrete is achieved.
Patent Information
- Application Number
- CN202411916600.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-22
AI Technical Summary
It is difficult for the prior art to simultaneously realize the resource utilization of solid waste materials and improve the permanent self-repair and waterproofing effect of cement-based permeable crystalline materials in concrete structures.
The solid waste-based permeable crystal waterproof functional aggregate is adopted. The aggregate has a spherical core-shell structure. The core layer is made of solid waste-based skeleton material and excitatory functional components. The shell layer is made of permeable crystal active repair components. The solid waste material is converted into functional aggregate with gelled structure through excitation theory, and the functional aggregate is incorporated into the concrete to improve its waterproof performance.
It realizes the low-carbon resource utilization of solid waste materials, improves the fluidity, compressive resistance and permeability of concrete, and provides good self-healing and restoration throughout the life cycle, enhancing the durability of concrete.
Smart Images

Figure CN119859029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a solid waste-based permeable crystallization waterproof functional aggregate and a preparation method and application thereof. Background Art
[0002] Based on the current status of the stock, increase and comprehensive utilization rate of bulk solid waste in my country, if bulk solid waste materials can be recycled under low-carbon production conditions through technical means, it will be of great benefit to the transformation of solid waste materials into new uses, carbon fixation and emission reduction.
[0003] The application of commercial concrete in my country has a history of 40-50 years, but the cracking and leakage of underground waterproof concrete structures, which have been used for the same period of time, is also an important factor affecting the safety, applicability and durability of many engineering structures. The "General Specification for Waterproofing of Buildings and Municipal Engineering" (GB 55030-2022) issued in 2022 requires that the design working life of underground engineering waterproofing should not be less than the design working life of engineering structures, so an effective waterproof structure throughout the life cycle of a building is an important support for improving the vitality of the building. Compared with the shortcomings of flexible external waterproofing materials, such as poor durability, complex construction and long construction period, cement-based penetrating crystalline waterproofing material is a rigid waterproof layer acting on the concrete structure itself. The construction and closure of the waterproof layer are achieved during the concrete pouring process. The active components can penetrate and crystallize in the concrete through the carrier to form water-insoluble crystals to block capillary pores and cracks. Moreover, the active components based on the complexation-precipitation principle can be replaced after the crystals are formed. It can be simply understood as a role similar to that of a "catalyst". The reaction itself will not consume the active components, so it can serve in concrete for a long time and can play an anti-cracking and anti-seepage role within the design service life of the entire structure.
[0004] In the prior art, such as CN111087213A, solid waste materials are pelletized to prepare ceramsite for lightweight aggregate concrete. The production process requires long-term high temperature and high pressure (180℃±10℃, 1.0MPa for 8h-10h), which consumes a lot of energy. CN114370170A discloses a cement-based penetrating crystallization waterproofing agent, which can only be used to passively repair observable cracks manually, and requires an operating surface and dedicated maintenance and construction personnel, which loses the self-repairing advantage of cement-based penetrating crystallization materials. CN113045283A discloses an intelligent trigger-type concrete micro-crack self-repairing microcapsule and a preparation method thereof, but it never mentions the dosage of the self-repairing capsule in concrete, because the wall materials of the microcapsule are ethyl cellulose, chitosan and hydroxypropyl methylcellulose, these three organic substances cannot participate in the hydration reaction of concrete, will cause structural weak areas to affect the strength of concrete, the solid dosage can only be controlled within a limited range, and the low dosage results in a small amount of effective repair components in the core material in the entire concrete structure, making it difficult to achieve an ideal repair effect. Therefore, there is an urgent need to develop a solid waste-based permeable crystallizing waterproof functional aggregate to achieve underground waterproof concrete that has the dual functions of carbon fixation and emission reduction and permanent waterproofing. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present invention provides a solid waste-based permeable crystallization waterproof functional aggregate and its preparation method and application, aiming to solve the technical problem that the existing technology is difficult to simultaneously achieve the resource utilization of solid waste materials and improve the permanent self-repairing waterproof effect of cement-based permeable crystallization materials in concrete structures.
[0006] In a first aspect, the present invention provides a solid waste-based permeable crystallization waterproof functional aggregate, the functional aggregate having a spherical core-shell structure, the raw materials for preparing the core layer include a solid waste-based skeleton material and an excitatory functional component, and the raw materials for preparing the shell layer include a permeable crystallization active repair component; the mass ratio of the solid waste-based skeleton material, the excitatory functional component and the permeable crystallization active component is 75-82:14-21:3-6; Solid waste-based skeleton materials include silicate cement, mineral powder and solid waste cementitious materials; The infiltration crystallization active repair component includes silicate cement, chelating agent, dodecylethoxysulfobetaine, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; The stimulating functional components include at least one of quicklime, carbide slag, sodium silicate, sodium carbonate, sodium hexametaphosphate, sodium metaaluminate and sodium phosphate.
[0007] Preferably, the solid waste-based skeleton material comprises the following components by weight: 5-15 parts of Portland cement, 20-25 parts of mineral powder and 65-90 parts of solid waste cementitious material.
[0008] Preferably, the solid waste cementitious material includes at least one of red mud, lithium slag, steel slag, water slag, desulfurized gypsum, fly ash, and iron ore tailings powder.
[0009] Preferably, the complexing agent in the infiltration crystallization active repair component includes zirconium silicone, sodium citrate, sodium gluconate and tetrasodium ethylenediaminetetraacetic acid.
[0010] Preferably, the infiltration crystallization active repair component includes the following components by weight: 40-45 parts of silicate cement, 20-25 parts of zirconium silicone, 10-18 parts of sodium citrate, 3-8 parts of sodium gluconate, 10-20 parts of tetrasodium ethylenediaminetetraacetic acid, 2.2-3.5 parts of dodecylethoxysulfobetaine, 1.1-2.6 parts of sodium dodecyl sulfate and 1.2-2.4 parts of sodium dodecylbenzene sulfonate.
[0011] Preferably, the particle size of the solid waste-based permeable crystallized waterproof functional aggregate is 3 to 25 mm.
[0012] In a second aspect, the present invention provides a method for preparing a solid waste-based permeable crystallization waterproof functional aggregate, comprising the following steps: The solid waste-based skeleton material and the excitatory functional component are mixed to obtain a pre-homogenized core layer material; Mixing silicate cement, a complexing agent, dodecylethoxysulfobetaine, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate to obtain a permeable crystallization active repair component; The pre-homogenized core layer material is spherically granulated, and the first atomized water is sprayed at the same time to form core layer skeleton material balls, until the particle size of the core layer skeleton material balls reaches 92% to 95% of the target particle size, and the osmotic crystallization active repair component is added to the core layer skeleton material balls to continue spherical granulation, and the second atomized water is sprayed at the same time until the material balls of the target particle size are obtained; The balls of target particle size are covered and maintained to retain moisture to obtain solid waste-based permeable, crystallized, waterproof functional aggregate; the curing time is ≥ 7 days.
[0013] Preferably, the target particle size is 3 to 25 mm.
[0014] Preferably, the mass of the first atomized water is 12% to 15% of the mass of the pre-homogenized core layer material, and the mass of the second atomized water is 15% to 20% of the mass of the osmotic crystallization active repair component.
[0015] Preferably, the mixing speed when the solid waste-based skeleton material and the excitatory functional components are mixed is 20-50 r / min, and the mixing time is 15-20 min.
[0016] Preferably, the mixing speed of silicate cement, complexing agent, dodecylethoxysulfobetaine, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate is 10-50 r / min, and the mixing time is 20-30 min.
[0017] In a third aspect, the present invention provides an application of a solid waste-based permeable, crystallized, waterproof functional aggregate in the preparation of concrete.
[0018] In a fourth aspect, the present invention provides a concrete, wherein the raw materials for preparing the concrete include water, cement, fine aggregate, coarse aggregate and the solid waste-based permeable crystallization waterproof functional aggregate described in the first aspect of the present invention; the particle size ranges of the solid waste-based permeable crystallization waterproof functional aggregate include 3-5mm, 6-10mm, 11-15mm, 16-20mm, and 21-25mm.
[0019] Preferably, the mass ratio of solid waste-based permeable crystallization waterproof functional aggregate with a particle size range of 3-5mm to fine aggregate is 0.15~0.3; the mass ratio of the total mass of solid waste-based permeable crystallization waterproof functional aggregate with a particle size range of 6-10mm, 11-15mm, 16-20mm, and 21-25mm to coarse aggregate is 0.15~0.3; the particle size of the fine aggregate is ≤5mm; the particle size of the coarse aggregate is 5~150mm.
[0020] Fine aggregate refers to gravel or crushed stone with a particle size of less than 5mm used in the preparation of concrete. Coarse aggregate refers to aggregate with a particle size greater than 5mm. Coarse aggregate is divided into small stone (5~20mm), medium stone (20~40mm), large stone (40~80mm), and extra large stone (80~150mm) according to particle size.
[0021] The present invention provides a solid waste-based permeable crystallization waterproof functional aggregate, which has a spherical core-shell structure, wherein the raw materials for preparing the core layer include solid waste-based skeleton materials and excitatory functional components, and the raw materials for preparing the shell layer include permeable crystallization active repair components. The main component of the solid waste-based skeleton material is solid waste gelling material, which includes one or a combination of red mud, lithium slag, steel slag, water slag, desulfurized gypsum, fly ash, and iron tailings powder. By identifying and analyzing the core mineral composition of these solid waste materials, and adding corresponding quicklime, carbide slag, sodium silicate, sodium carbonate, sodium hexametaphosphate, sodium metaaluminate, sodium phosphate and other excitatory functional components, the CSH gel generated by the tetracoordinate isomorphism effect of silicon in the solid waste material and the calcium sulfonate generated by the double salt effect can be used under the participation of water, so that the solid waste material can generate a cementitious structure similar to cement without autoclaving, and reach a strength similar to that of cement hydration. By using this excitation theory, a large amount of solid waste materials can be recycled under low-carbon production conditions and converted into a skeleton structure of functional aggregates, whose cylinder pressure strength can reach more than 10MPa, which not only realizes the reuse of solid waste, but also can be used as a substitute aggregate for concrete, reducing the amount of natural mineral aggregates mined. The excited solid waste functional aggregate has passive hydration power, and has better compatibility and symbiosis with cement-based materials in concrete, which increases the interfacial adhesion between aggregates and cement paste in concrete, reduces the weak area of the interface, and improves the density and strength of concrete. In addition, the solid waste-based permeable crystallization waterproof functional aggregate prepared in the ball-disc granulator is spherical, which reduces the thixotropic shear force and rolling friction of concrete in the plastic state, makes the concrete have better fluidity during mixing, pumping, and pouring, and improves the construction and applicability of concrete.
[0022] The shell layer of the solid waste-based permeable crystallization waterproof functional aggregate of the present invention is a permeable crystallization active component. Based on the functional aggregate of the present invention replacing 15% to 30% of the coarse and fine aggregates in concrete, a large amount of permeable crystallization active components will be evenly dispersed in the concrete. When cracks and leakage occur at any position of the concrete during service, a large amount of repair components can respond quickly: the zirconium silicone, sodium citrate, sodium gluconate, and tetrasodium ethylenediaminetetraacetic acid in the permeable crystallization active components can react with the calcium ions and hydration product Ca(OH)2 in the unhydrated cement to form a water-soluble, unstable calcium complex. At the same time, dodecylethoxysulfobetaine, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate can reduce the surface tension of water inside concrete and improve the diffusion and transmission efficiency of calcium complexes. In this way, calcium complexes diffuse and penetrate into concrete pores and cracks with water under the action of capillary pores and concentration differences. Under the difference in solubility, the active components in the calcium complexes are replaced by silicate ions in cement hydration products to generate hydrated calcium silicate to fill and block cracks and pores, while the active substances are replaced to continue to generate calcium complexes that diffuse and penetrate in concrete, continuously repairing cracked and leaking parts of concrete. The self-healing properties of penetrating crystallization materials in concrete protect concrete from the hidden dangers of structural safety and applicability caused by cracking and water seepage. At the same time, the dense concrete structure can improve the durability of concrete against chloride ion erosion, sulfate erosion, and carbonization.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a solid waste-based permeable crystallized waterproof functional aggregate, which, when added to concrete, improves the fluidity and compressive properties of the concrete, can provide good healing and repair effects over the entire life cycle of the concrete, and enhances the concrete's resistance to sulfate erosion, chloride ion erosion, cracking, and other properties.
[0024] (2) The solid waste-based permeable crystallized waterproof functional aggregate provided by the present invention is spherical, which reduces the thixotropic shear force and rolling friction of concrete in the plastic state, makes the concrete have better fluidity during mixing, pumping and pouring, and improves the workability and applicability of the concrete.
[0025] (3) The solid waste-based permeable crystallization waterproof functional aggregate provided by the present invention has a spherical core-shell structure. The raw materials for preparing the core layer include solid waste-based skeleton materials and stimulating functional components, and the raw materials for preparing the shell layer include permeable crystallization active repair components. Among them, the solid waste gel material in the solid waste-based skeleton material of the core layer has the advantages of low carbon fixation and heavy metal solidification. The stimulating functional components can stimulate the activity of the solid waste material without pressure steaming, so that the solid waste-based skeleton material can produce strength. When it is added to concrete in the form of aggregate, it can not only reduce the demand for natural aggregates, but also improve the bonding performance of the aggregate interface area and reduce the interface defects of aggregates and cementitious materials. At the same time, the shell layer is rich in a large number of permeable crystallization active components. When cracks appear in the concrete during service or harmful ions invade, the cement-based permeable crystallization active repair components can generate water-insoluble crystals, which fill and block the capillary channels and cracks inside the concrete, prevent water and harmful substances from eroding, and improve the compactness and impermeability of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical picture of the solid waste-based permeable crystallization waterproof functional aggregate according to Example 1 of the present invention; Figure 2 This is a SEM image of the solid waste-based permeable crystallized waterproof functional aggregate in the concrete internal interface transition zone of Example 1 of the present invention; Figure 3 This is a SEM image of the solid waste-based permeable crystallized waterproof functional aggregate in the concrete interface transition zone of Example 2 of the present invention. DETAILED DESCRIPTION
[0027] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0028] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0029] Example 1 A solid waste-based permeable crystallization waterproof functional aggregate, comprising the following components by weight: Solid waste-based skeleton materials: 7 parts of silicate cement, 20 parts of mineral powder, 68 parts of solid waste cementitious materials (30 parts of red mud, 38 parts of lithium slag); Exciting functional components: 2 parts of carbide slag, 3 parts of sodium aluminate; Penetration crystallization active repair components: 40 parts of silicate cement, 24 parts of zirconium silicone, 12 parts of sodium citrate, 4 parts of sodium gluconate, 15 parts of tetrasodium ethylenediaminetetraacetic acid, 2.3 parts of dodecylethoxysulfobetaine, 1.4 parts of sodium lauryl sulfate, 1.3 parts of sodium dodecylbenzene sulfonate; The mass ratio of solid waste-based skeleton material, stimulating functional component and infiltration crystallization active repair component is 80:18:5.
[0030] The method for preparing the solid waste-based permeable crystallization waterproof functional aggregate comprises the following steps: S1. Weigh the solid waste-based skeleton materials (Portland cement, mineral powder, red mud, lithium slag) and the excitatory functional components (carbide slag, sodium aluminate) by weight, and mix them at 40 r / min for 15 minutes using a mixer to prepare a pre-homogenized solid waste-based skeleton material; S2. Weigh silicate cement, zirconium silicone, sodium citrate, sodium gluconate, tetrasodium ethylenediaminetetraacetic acid, dodecylethoxysulfobetaine, sodium dodecyl sulfate, and sodium dodecylbenzenesulfonate in parts by weight, and mix them at 40 r / min for 20 min using a mixer to obtain a permeation crystallization active repair component; S3. Divide the pre-homogenized solid waste-based skeleton material and the infiltration crystallization active repair component into 5 equal parts, and use them to make 5 kinds of pellets with different particle sizes: The preparation of the pellets with a designed finished particle size of 3-5 mm is as follows: the ball-disc granulator is started, the pre-homogenized solid waste-based skeleton material is uniformly and dispersedly added to the ball-disc granulator, the rotation speed and angle of the ball-disc are adjusted, and atomized water with a mass of 15 wt% of the mass of the pre-homogenized solid waste-based skeleton material is sprayed at the same time to prepare the core layer skeleton pellets. When the particle size of the core layer skeleton pellets reaches 2.79-4.65 mm, the infiltration crystallization active repair component is added to the ball-disc granulator, the rotation speed and angle of the ball-disc are adjusted, and atomized water with a mass of 16 wt% of the mass of the infiltration crystallization active repair component is sprayed at the same time to obtain pellets with a particle size of 3-5 mm; Design the preparation of pellets with a finished particle size of 6-10 mm: start the ball-disc granulator, add the pre-homogenized solid waste-based skeleton material evenly and dispersedly into the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 15wt% of the mass of the pre-homogenized solid waste-based skeleton material to prepare core layer skeleton pellets. When the particle size of the core layer skeleton pellets reaches 5.58-9.30 mm, add the infiltration crystallization active repair component to the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 16wt% of the mass of the infiltration crystallization active repair component to obtain pellets with a particle size of 6-10 mm; Design the preparation of pellets with a finished particle size of 11-15 mm: start the ball-disc granulator, add the pre-homogenized solid waste-based skeleton material evenly and dispersedly into the ball-disc granulator, adjust the ball-disc rotation speed and angle, and spray atomized water with a mass of 15 wt% of the mass of the pre-homogenized solid waste-based skeleton material to prepare core layer skeleton pellets. When the particle size of the core layer skeleton pellets reaches 10.23-13.95 mm, add the infiltration crystallization active repair component to the ball-disc granulator, adjust the ball-disc rotation speed and angle, and spray atomized water with a mass of 16 wt% of the mass of the infiltration crystallization active repair component to obtain pellets with a particle size of 11-15 mm; Design the preparation of pellets with a finished particle size of 16-20 mm: start the ball-disc granulator, add the pre-homogenized solid waste-based skeleton material evenly and dispersedly into the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 15 wt% of the mass of the pre-homogenized solid waste-based skeleton material to prepare core layer skeleton pellets. When the particle size of the core layer skeleton pellets reaches 14.88-18.60 mm, add the infiltration crystallization active repair component to the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 16 wt% of the mass of the infiltration crystallization active repair component to obtain pellets with a particle size of 16-20 mm; Design the preparation of pellets with a finished particle size of 21-25 mm: start the ball-disc granulator, add the pre-homogenized solid waste-based skeleton material evenly and dispersedly into the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 15 wt% of the mass of the pre-homogenized solid waste-based skeleton material to prepare the core layer skeleton pellets. When the particle size of the core layer skeleton pellets reaches 19.53-23.25 mm, add the infiltration crystallization active repair component to the ball-disc granulator, adjust the ball-disc speed and angle, and spray atomized water with a mass of 16 wt% of the mass of the infiltration crystallization active repair component to obtain pellets with a particle size of 21-25 mm; S4. Cover and maintain the five prepared balls with different particle sizes for 7 days to obtain solid waste-based permeable, crystallized and waterproof functional aggregates.
[0031] Example 2 A solid waste-based permeable crystallization waterproof functional aggregate, comprising the following components by weight: Solid waste-based skeleton materials: 5 parts of silicate cement, 20 parts of mineral powder, 65 parts of solid waste cementitious materials (30 parts of steel slag, 22 parts of water slag, 13 parts of desulfurized gypsum); Exciting functional components: 2 parts of quicklime, 3 parts of sodium silicate, 1 part of sodium carbonate; Penetration crystallization active repair components: 43 parts of silicate cement, 20 parts of zirconium silicone, 10 parts of sodium citrate, 3 parts of sodium gluconate, 10 parts of tetrasodium ethylenediaminetetraacetic acid, 2.2 parts of dodecylethoxysulfobetaine, 1.1 parts of sodium lauryl sulfate, 1.2 parts of sodium dodecylbenzene sulfonate; The mass ratio of solid waste-based skeleton material, stimulating functional components, and infiltration crystallization active repair components is 75:14:3.
[0032] The preparation method of the solid waste-based permeable crystallization waterproof functional aggregate is basically the same as that in Example 1.
[0033] Example 3 A solid waste-based permeable crystallization waterproof functional aggregate, comprising the following components by weight: Solid waste-based skeleton materials: 15 parts of silicate cement, 25 parts of mineral powder, 90 parts of solid waste cementitious materials (35 parts of red mud, 30 parts of slag, 18 parts of fly ash, 7 parts of iron ore tailings powder); Exciting functional components: 2 parts of carbide slag, 2 parts of sodium hexametaphosphate, 1 part of sodium metaaluminate, and 1 part of sodium phosphate; Penetration crystallization active repair components: 45 parts of silicate cement, 25 parts of zirconium silicone, 18 parts of sodium citrate, 8 parts of sodium gluconate, 20 parts of tetrasodium ethylenediaminetetraacetic acid, 3.5 parts of dodecylethoxysulfobetaine, 2.6 parts of sodium lauryl sulfate, 2.4 parts of sodium dodecylbenzene sulfonate; The mass ratio of solid waste-based skeleton material, stimulating functional components, and infiltration crystallization active repair components is 82:21:6.
[0034] The preparation method of the solid waste-based permeable crystallization waterproof functional aggregate is basically the same as that in Example 1.
[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the mass ratio of the solid waste-based skeleton material, the stimulating functional component, and the infiltration crystallization active repair component is 80:10:10; the preparation method of the solid waste-based infiltration crystallization waterproof functional aggregate is the same as that in Example 1.
[0036] Comparative Example 2 The formula of the solid waste-based permeable crystallized waterproof functional aggregate in this comparative example is the same as that in Example 1. The difference between this comparative example and Example 1 is that in the preparation method of the solid waste-based permeable crystallized waterproof functional aggregate, when manufacturing 5 solid waste-based permeable crystallized waterproof functional aggregates with different particle sizes in step S3: the pre-homogenized solid waste-based skeleton material and the permeable crystallized active repair component are added to the ball-disc granulator at the same time and evenly dispersedly, the rotation speed and angle of the ball-disc are adjusted, and atomized water with a mass of 15 wt% of the total mass of the pre-homogenized solid waste-based skeleton material and the permeable crystallized active repair component is sprayed at the same time to obtain solid waste-based permeable crystallized waterproof functional aggregates with different particle sizes.
[0037] Comparative Example 3 The formula of the solid waste-based permeable crystallization waterproof functional aggregate in this comparative example is the same as that in Example 1. The difference between this comparative example and Example 1 is that the functional aggregate finished product has only two particle size ranges, namely 3-5 mm and 11-15 mm.
[0038] Test Example 1 Effect of the composition and structure of solid waste-based permeable crystallization waterproof functional aggregate on the performance of concrete mixed with solid waste-based permeable crystallization waterproof functional aggregate Table 1 shows the C40 concrete mix ratio, which is divided into a control group and an experimental group. In the experimental group, 20% of the mass of fine aggregate in the concrete mix was added with solid waste-based permeable crystallization waterproof functional aggregate with a particle size of 3-5 mm prepared in each embodiment or comparative example; 20% of the mass of coarse aggregate in the concrete mix was evenly added with solid waste-based permeable crystallization waterproof functional aggregate with a particle size of 6-10 mm, 11-15 mm, 16-20 mm, and 21-25 mm prepared in each embodiment or comparative example. The concrete without solid waste-based permeable crystallization waterproof functional aggregate was used as the control group.
[0039] The concrete of the control group and each experimental group was evaluated for slump, expansion, compressive strength, impermeability, sulfate erosion resistance, chloride ion penetration resistance, and frost resistance. The specific process is as follows: The C40 concrete mix ratio is designed for slump, expansion, compressive strength, sulfate erosion resistance, chloride ion penetration resistance and frost resistance tests, see Table 1: Table 1 C40 concrete mix proportion (kg / m 3 )
[0040] Since the "Cement-based Penetrating Crystalline Waterproof Material" (GB 18445-2012) has a recommended mix ratio for the benchmark concrete for testing the anti-seepage performance, and requires the benchmark concrete to have an anti-seepage pressure of 0.4MPa±0.1MPa, the mix ratio is designed separately for the anti-seepage test, see Table 2: Table 2 Concrete mix ratio for impermeability test (kg / m 3 )
[0041] The slump and expansion tests were conducted in accordance with the requirements of the Standard for Test Methods for Ordinary Concrete Mixtures (GB / T 50080-2016); the compressive strength test was conducted in accordance with the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T50081-2019); the impermeability test was conducted in accordance with the requirements of the Cement-based Penetrating Crystalline Waterproof Material (GB 18445-2012); the sulfate erosion resistance, chloride ion penetration resistance, and frost resistance tests were conducted in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T 50082-2009), of which the chloride ion penetration test adopted the RCM method, and the frost resistance test adopted the quick freezing method. The specific experimental results are shown in Table 3. Table 3 Test results of examples and comparative examples
[0042] It can be seen from the experimental results in Table 3 that the slump and expansion of the concrete prepared by adding the solid waste-based permeable crystallization waterproof functional aggregate described in Examples 1 to 3 of the present invention are better than those of the control group, indicating that the solid waste-based permeable crystallization waterproof functional aggregate prepared by the present invention can improve the high fluidity of the concrete; the compressive strength of the concrete prepared by adding the solid waste-based permeable crystallization waterproof functional aggregate described in Examples 1 to 3 of the present invention is significantly higher than that of the control group, indicating that the concrete is more compact and has fewer internal pores and defects; The waterproof functional aggregate greatly improves the anti-seepage performance of the concrete, and the second anti-seepage pressure of the specimen after being permeable after 28 days of testing and then cured to 56 days of age is higher than that of 28 days, indicating that the penetrating crystallization repair component in the present invention plays an ideal self-healing repair role in the concrete, so that the concrete can be self-repaired and reinforced to be dense and anti-seepage after the generation of crack seepage channels; the anti-sulfate erosion, anti-chloride ion penetration and anti-freezing experiments show that the concrete prepared by adding the solid waste-based penetrating crystallization waterproof functional aggregate described in Examples 1 to 3 of the present invention has good durability. The results of Comparative Example 2 and Example 1 show that if the pre-homogenized solid waste-based skeleton material and the infiltration crystallization active repair component are added to the ball-disk granulator at the same time, the original ratio of the solid waste cementitious material and the stimulating functional component is changed due to the early addition of the infiltration crystallization active repair component, and they cannot be evenly contacted and fully reacted, resulting in the activity of the skeleton material not being fully stimulated, and the strength of the generated core layer skeleton ball is low, thereby reducing the compressive strength of the prepared concrete, and because part of the infiltration crystallization active repair component is wrapped inside the ball, the active repair component enrichment zone of the ball shell cannot be formed, and it is difficult to be in the cement-based slurry and The interface transition zone of the aggregate fully exerts the penetration and repairing effect, resulting in the reduction of the anti-permeability and durability of the concrete; the results of comparative example 3 and embodiment 1 show that if the single-size functional aggregate directly replaces the original concrete aggregate, it is difficult to form a continuous and reasonable particle grading, resulting in poor workability of the concrete, which is manifested in comparative example 3, that is, the fluidity is reduced and the wrapping is deteriorated, resulting in the exposure of large-size aggregate after mixing, which not only affects the workability but also reduces the uniformity of the formed concrete specimen, forming a small-size aggregate and cement-based slurry enrichment area, thereby affecting the density of the overall concrete specimen and reducing the strength, anti-permeability and durability.
[0043] Test Example 2 Effect of the amount of solid waste-based permeable crystallization waterproof functional aggregate on the performance of concrete mixed with solid waste-based permeable crystallization waterproof functional aggregate Table 4 shows the C40 concrete mix ratio, which is divided into a control group and an experimental group. In the experimental group, 15%, 20%, and 30% of the mass of fine aggregate in the concrete mix were added to the solid waste-based permeable crystallization waterproof functional aggregate with a particle size of 3-5 mm prepared in Example 1; 15%, 20%, and 30% of the mass of coarse aggregate in the concrete mix were added to the solid waste-based permeable crystallization waterproof functional aggregate with a particle size of 6-10 mm, 11-15 mm, 16-20 mm, and 21-25 mm prepared in Example 1; and the concrete without the solid waste-based permeable crystallization waterproof functional aggregate was used as the control group.
[0044] Table 4 C40 concrete mix ratio (kg / m 3 )
[0045] Since the "Cement-based Penetrating Crystalline Waterproof Material" (GB 18445-2012) has a recommended mix ratio for the benchmark concrete for testing the anti-seepage performance, and requires the benchmark concrete to have an anti-seepage pressure of 0.4MPa±0.1MPa, a separate mix ratio is designed for the anti-seepage test, see Table 5: Table 5 Concrete mix ratio for anti-seepage test (kg / m 3 )
[0046] The slump and expansion tests were conducted in accordance with the requirements of the Standard for Test Methods for Ordinary Concrete Mixtures (GB / T 50080-2016); the compressive strength test was conducted in accordance with the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T50081-2019); the impermeability test was conducted in accordance with the requirements of the Cement-based Penetrating Crystalline Waterproof Material (GB 18445-2012); the sulfate erosion resistance, chloride ion penetration resistance, and frost resistance tests were conducted in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T 50082-2009), of which the chloride ion penetration test adopted the RCM method, and the frost resistance test adopted the quick freezing method. The specific experimental results are shown in Table 6. Table 6 Test results of examples and comparative examples
[0047] It can be seen from the experimental results in Table 6 that the functional aggregate of the present invention can replace 15% to 30% of the coarse and fine aggregates in concrete to improve the fluidity, impermeability and durability of concrete, especially when the functional aggregate replaces 20% of the coarse and fine aggregates in concrete, the effect is better.
[0048] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.
Claims
1. A solid waste-based permeable crystallization waterproof functional aggregate, characterized in that: The functional aggregate has a spherical core-shell structure, the raw materials for preparing the core layer include solid waste-based skeleton materials and excitatory functional components, and the raw materials for preparing the shell layer include infiltration crystallization active repair components; the mass ratio of the solid waste-based skeleton materials, the excitatory functional components and the infiltration crystallization active components is 75-82:14-21:3-6; The solid waste-based skeleton material includes silicate cement, mineral powder and solid waste gelling material; The infiltration crystallization active repair component includes silicate cement, complexing agent, dodecylethoxysulfobetaine, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; The excitatory functional component includes at least one of quicklime, carbide slag, sodium silicate, sodium carbonate, sodium hexametaphosphate, sodium metaaluminate, and sodium phosphate.
2. The solid waste-based permeable crystallization waterproof functional aggregate according to claim 1, characterized in that: The solid waste-based skeleton material comprises the following components by weight: 5-15 parts of silicate cement, 20-25 parts of mineral powder and 65-90 parts of solid waste cementitious material.
3. The solid waste-based permeable crystallization waterproof functional aggregate according to claim 1, characterized in that: The solid waste cementitious material includes at least one of red mud, lithium slag, steel slag, water slag, desulfurized gypsum, fly ash, and iron tailings powder.
4. The solid waste-based permeable crystallization waterproof functional aggregate according to claim 1, characterized in that: The complexing agent in the infiltration crystallization active repair component includes zirconium silicone, sodium citrate, sodium gluconate and tetrasodium ethylenediaminetetraacetic acid.
5. The solid waste-based permeable crystallization waterproof functional aggregate according to claim 4, characterized in that: The infiltration crystallization active repair component includes the following components by weight: 40-45 parts of silicate cement, 20-25 parts of zirconium silicone, 10-18 parts of sodium citrate, 3-8 parts of sodium gluconate, 10-20 parts of tetrasodium ethylenediaminetetraacetic acid, 2.2-3.5 parts of dodecylethoxysulfobetaine, 1.1-2.6 parts of sodium dodecyl sulfate and 1.2-2.4 parts of sodium dodecylbenzene sulfonate.
6. A method for preparing a solid waste-based permeable crystallization waterproof functional aggregate as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The solid waste-based skeleton material and the excitatory functional component are mixed to obtain a pre-homogenized core layer material; Mixing silicate cement, a complexing agent, dodecylethoxysulfobetaine, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate to obtain a permeable crystallization active repair component; The pre-homogenized core layer material is spherically granulated, and the first atomized water is sprayed at the same time to form core layer skeleton balls, until the particle size of the core layer skeleton balls reaches 92% to 95% of the target particle size, and the osmotic crystallization active repair component is added to the core layer skeleton balls to continue spherical granulation, and the second atomized water is sprayed at the same time until balls of the target particle size are obtained; The balls of the target particle size are covered and maintained to retain moisture to obtain solid waste-based permeable, crystallized, waterproof functional aggregate; the curing time is ≥ 7 days.
7. The method for preparing a solid waste-based permeable crystallization waterproof functional aggregate according to claim 6, characterized in that: The target particle size is 3-25 mm.
8. Use of a solid waste-based permeable crystallization waterproof functional aggregate as described in any one of claims 1 to 5 in the preparation of concrete.
9. A concrete, characterized in that: The raw materials for preparing the concrete include water, cement, fine aggregate, coarse aggregate and the solid waste-based permeable crystallization waterproof functional aggregate according to any one of claims 1 to 5; the particle size range of the solid waste-based permeable crystallization waterproof functional aggregate includes 3-5mm, 6-10mm, 11-15mm, 16-20mm, and 21-25mm.
10. The concrete according to claim 9, characterized in that: The mass ratio of the solid waste-based permeable crystallization waterproof functional aggregate with a particle size range of 3-5mm to the fine aggregate is 0.15-0.3; the mass ratio of the total mass of the solid waste-based permeable crystallization waterproof functional aggregate with a particle size range of 6-10mm, 11-15mm, 16-20mm, and 21-25mm to the coarse aggregate is 0.15-0.3; the particle size of the fine aggregate is ≤5mm; the particle size of the coarse aggregate is 5-150mm.
Citation Information
Patent Citations
Method for preparing high-strength slag silicate ceramsite by pre-hydrated cement paste spray balling process
CN111087213A
Intelligent triggering type concrete microscopic crack self-repairing microcapsule and preparation method thereof
CN113045283A
Preparation of capillary crystalline waterproof agent
CN114370170A